Building Competitive Advantage Through Strategy Map and Balanced Scorecard in Improving Company Performance - Priliska, Arstianti Dienar; Kurniadewi, Maulida; Winarno, Fadiah Shabrina (Devotion : Journal of Research and Community Service, 2023)
The purpose of this research is to identify strategy maps for PT. TA company based on the problems faced by the company, to identify the right balanced scorecard design for PT. TA, to find out the best competitive strategy that can be used by PT. TA to be able to compete with other heavy equipment rental companies in Central Java. The research approach used is a qualitative research method. The results show PT. TA faces problems of dependence on a single product, low production efficiency, and high production costs. To overcome this, they can implement several strategies. First, they can open new markets or explore markets that have not been optimally exploited through a map strategy. In addition, they can also develop new products or product variations of existing products, as well as product diversification. In addition, companies need to improve production processes, increase the efficiency of resource use, improve product quality, and improve production technology in order to reduce high production costs and increase production efficiency. By implementing these strategies, PT. TA can increase competitiveness and ensure the continuity of the company's business in the long term. PT. TA can adopt a Balanced Scorecard (BSC) design to continuously monitor strategy implementation. By using BSC, companies can ensure that all important aspects of business are well integrated in the company's strategy. Business goals can be achieved in a directed and measurable manner through the implementation of the BSC.